The Activity of Lenglengan Leaf Extract (Leucas lavandulifolia Sm.) as an Antibacterial for Staphylococcus aureus - Virgolie Diknas Ximenis; Refli Refli; Djeffry Amalo; Alfred Dima; Rony Mauboy; Maria Ruma (Biology Education Study Program, Faculty of Teacher Training and Education, University of Mataram, Indonesia, 2022)
Dafala village is one of the villages in NTT that uses lenglengan leaves as traditional medicine to treat diseases such as coughs, TBC, diarrhea and back pain.This present research aims to know the bioactive compounds and composition of the bioactive contained in Lenglengan (Leucas lavandulifolia Sm.) leaf extract, and too know the effectiveness of lenglengan leaf extract in inhibiting Staphyloccocus areus bacteria. We extracted leaves of Lenglengan by maceration method using ethanol. The extract was obtained and then tested in a qualitative way to determine the bioactive compounds are made by using reagents. While in the quantitative test to Determine of levels of flavonoids, phenols and tannins using UV-Vis spectrophotometry method, alkaloids and saponins using the gravimetric method. The Antibacterial test was carried out by disc paper method. Paper discs containing extract concentrations: 12.5%, 25%, 50%, 62.5% and 75%, positive control (gentamicin) and negative control (aquadest) were placed on MHA media containing S. aureus suspension, incubated at 37°C for 24 hours and then the diameter of the inhibition was observed. Qualititive test result show that the lenglengan leaf extract contains 5 bioactive compounds include alkaloids, flavonoids, saponins, tannins, and phenols. The composition of bioactive compounds in Lenglengan leaf extract: flavonoids 23.93%, saponins: 19.05%, alkaloids: 15.28%, tannins: 5.81%, and phenols: 2,335%. The atibacterial result reveal that lenglengan leaf extract was significantly affect in inhibiting Staphylococcus aureus. The higher concentration of extract lenglengan leaves used, the higher the inhibition zone produced. The highest level response inhibition showed from level of 12.5%: 11.3 mm, 25%: 12.4 mm, 50%: 13.43 mm, 62.5%: 14.43 mm and 75%: 15.58 mm, gentamicin: 17.4 mm aquades: 0 mm.